Earning a living in PNG: From subsistence to a cash economy - Curry, George; Koczberski, Gina; Lummani, Joachim; Ryan, S.; Bue, V. (Springer, 2012)
This chapter addresses the question of how individuals and families in rural PNG respond to major livelihood threats as they make the transition from a subsistence mode of life to become increasingly integrated into the global economy through export cash cropping. Two case studies are presented: cocoa farmers on the Gazelle Peninsula of East New Britain Province (ENB) and oil palm migrant farmers residing on the Hoskins Land Settlement Scheme in West New Britain Province (WNB). The cocoa farming community of Gazelle Peninsula began growing cocoa on their customary land in the 1950s with encouragement by the Australian administration. Since 2006 they have been confronted with an introduced cocoa pest, Cocoa Pod Borer (CPB), which is devastating their cocoa crop and livelihoods. The migrant oil palm farmers voluntarily took up State agricultural leases of 6 ha blocks in the late 1960s and early 1970s and are now experiencing population and resource pressures as their children marry and begin raising their own families on their parents’ blocks. By examining the pressures emerging among farming households as they make the transition to a market economy, the chapter highlights some of the key challenges and pressures of contemporary rural life for people in the Global South such as declining access to land, increased dependence on cash, fluctuating cash crop prices and changing lifestyle values.